Formation of a reversible cell in the electrolysis of molten silver nitrate - Triaca, Walter Enrique (1964)
In the electrolysis of pure molten silver nitrate with a silver cathode and a platinum anode at temperatures from 220 to 380°C a reversible cell is formed. When the system is electrolysed for a short time at a steady current density and then the current is interrupted, it tends to reach after a few seconds a reversible emf which is independent of the current density employed in the previous electrolysis. This emf is constant provided that the composition of the system is not altered. short-circuiting the cell repeatedly always leads to the same emf. The emf is related to the residual electrochemical cell formed during the electrolysis. The cell can be represented by the following scheme: Ag/AgNO3(l)/NO2,NO,O2/Pt. The reversible reactions involved in the cell are Ag + NO2 + 12O2 ⇌ AgNO3 and NO + 12O2 ⇌ NO2. The theoretical decomposition voltage of silver nitrate is coincident with the ones found experimentally, taking account of the actual concentrations of species involved in the reactions.